STRATEGIES TO IMPROVE EMPLOYEE PERFORMANCE IN THE TRANSPORTATION SERVICES OF ARMOR GROUP MALANG - Alfin Aulia Rachman; Abdul Khodir Djaelani; Pardiman (Pena Cendekia Insani, 2025)
Conflicts between extractive companies—particularly in the mining and palm oil sectors—and local communities in Indonesia represent a complex and enduring structural phenomenon. This study aims to identify and map scientific trends related to conflict management strategies in this context through a bibliometric approach. Data were collected from the Scopus database using selected keywords, covering publications from 2000 to 2024. The analysis was conducted using VOSviewer software, focusing on keyword mapping, publication productivity, and networks of author and institutional collaboration. The results revealed three major clusters in the literature: (1) social conflict and conflict management models, (2) sustainability dimensions and corporate social responsibility (CSR), and (3) stakeholder engagement and governance complexity. These findings underscore the importance of a multidimensional approach to understanding conflicts in the extractive sector and highlight a shift in academic focus toward community participation and value-based conflict resolution models. This study contributes to the mapping of scientific knowledge and offers strategic references for policymakers and industry practitioners in designing fair and sustainable conflict resolution approaches.